CHEMICAL COMPOSITION AND MECHANICAL PROPERTIES OF VARIOUS PARTS OF BIRCH WOOD - Vedernikov, Dmitriy Nikolaevich; Leontyev, Leonid Leonidovich; Morskoy-Lemeshko, Pavel Dmitrievich; Eltsova, Liubov Sergeevna (Химия растительного сырья, 2022)
The article compares mechanical parameters, group chemical compositions, iron content, lipid compositions before and after saponification, moisture, bulk density in three parts of Betula pubescens Ehrh. birch wooden parts: sapwood, false heartwood, false heartwood border. The strength properties of the false heartwood are worse than those of sapwood. The border of the false core is sometimes stronger than that of other parts. Evaluation is carried out in terms of hardness, flexural strength and compression strength. False heartwood, and even more so its border, contain more extractives extracted by ethanol, water, alkali solution, methylene chloride and less iron. The content of other components: cellulose, lignin, other polysaccharides differs, but less significantly. False heartwood border is heavier than the other wooden parts. Moisture content of the various parts decreases in the following order: false heartwood border, false heartwood, sapwood. The composition of the extractives extracted by methylene chloride is different in different parts. The composition is determined by gas-liquid chromatography-mass spectrometry before and after saponification of esters. Differences in sterols are given. An increased content of monoterpene alcohols and arylheptanoids is observed at the border. Differences in the properties of different wooden parts of a tree are explained by different amount and composition of extractives.